Nearest-neighbor field algorithm based on patchMatch for myocardial perfusion motion estimation/correction - Haider Ali Jasim Alshamary; Ahmad Sulaiman Abdullah; Sadeq Adnan Hbeeb (Bulletin of Electrical Engineering and Informatics, 2023)
Deformation correction and recovery of dynamic magnetic resonance images (DMRI) with low complexity algorithms without compromising image quality is a challenging problem. We proposed a motion estimation deformation-correction compressive sensing (DC-CS) scheme to recover dynamic images from its undersampled measurements. We simplify the complex optimization problem into three sub-problems. The contributions of this research are: introducing a global search strategy instead of the DC registration step, guaranteeing a non-explicit motion estimation that avoids any spatial alignment or registration of the images, and lowering the computational cost to the minimum by using PatchMatch (PM). The simulation result shows that the PM algorithm accelerates the recovery time without losing the quality in comparison with the DC algorithm.